Hydrochromic full-color MXene quantum dots through hydrogen bonding toward ultrahigh-efficiency white light-emitting diodes - Xu, Quan (2020)
Multiple-color emissive MXene quantum dots (MQDs) exhibit vast application prospects in various fields, including optoelectronics, bioimaging, and catalysis. However, the majority of the recent MQDs display limited maximum emission in the blue-light region. Herein, we employ the hydrogen bonds as an adjustment method to prepare novel full-color MQDs using Ti3C2 MXene as the starting material. By doping with sodium thiosulfate and ammonia water (sulfur-doped, nitrogen-doped), the maximum emission of the obtained MQDs demonstrates entire light spectrum covering from blue to orange light. Interestingly, the as-synthesized Ti3C2 MQDs aqueous solutions unveil multiple-color, excitation-independent emission wavelength and fluorescence (lifetime and quantum yield) enhancement compared with in the dry state. The fluorescence shift and enhancement are confirmed by comprehensive spectroscopic techniques (e.g. grazing incidence X-ray diffraction (GIXRD)) and complementary density functional theory (DFT) calculations. The results indicate that the construction of stalwart bridge-like hydrogen-bonded networks between the MQDs by highly ordered bound water on the doped MQDs surface can give rise to the immobilization of the Cdouble bondO and C–O bonds of the MQDs, thus strengthening the rigidity of the entire system. As a benefit of the bandgap emission, white light-emitting diodes (WLEDs) with stable emission color by directly utilizing MQDs as an active emission layer have been realized for the first time. As such, the as-prepared full-color MQDs developed herein can remarkably broaden the prospect of MXene 2D quantum dots (2D-QDs) in a myriad of technological applications such as electronics, batteries, bioimaging, and cancer therapy.